Public Administrative Efficiency within the Framework of the Neo-Weberian State an Analysis of the “One Application, Five Outcomes” Innovation by the Luwuk Branch of BPJS Kesehatan - Uzdatun Nabilah Fahmi; Bintoro Wardiyanto (Publikasi Indonesia, 2026)
This research aims to analyze the public service innovation